NEW DATA OF THE ANCIENT AND MODERN GLACIATION OF THE ARMENIAN HIGHLAND (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
New data of the ancient and modern glaciations of the Armenian Highlands are presented. From the second half of the nineteenth century a decrease in the area of modern glaciation of the highlands is noted, however, since 1980, the rate of glacier melting on the Ararat mountain turned out to be the lowest over the entire observation period. For the first time, according to the characteristic relief of the cirque moraines of Aragats, four stages of retreat of the Wurm glacier were identified, and the age of periods of warming and humidification of the climate and the formation of lakes was determined from the 14C radiocarbon dating of bottom sediments of intermorainal lakes.
Keywords: Armenian highland; cirque moraines; climate; glaciations; glaciers melting